Modulation of Long Non-coding RNA FAS-AS1/FAS/Caspase3 Axis in Endometriosis: A Cross-sectional Study - Amir Hossein Shayanfard; Zivar Salehi; Farhad Mashayekhi; Ziba Zahiri (Journal of Human Reproductive Sciences)
Background: An increasing number of studies have demonstrated that excessive proliferation and apoptosis play a pivotal role in the development of endometriosis. Aim: The aim of the study was to evaluate the expression of long non-coding RNA (lncRNA) FAS-AS1, FAS, soluble Fas (sFas) and caspase-3 in patients with different stages of endometriosis. Setting and Design: The design of the study was a cross-sectional study. Materials and Methods: The relative expression of lncRNA FAS-AS1 and FAs gene was evaluated by the quantitative real-time polymerase chain reaction in 60 ectopic endometrial samples from women with endometriosis in relation to 85 normal endometrial tissues from healthy women, whereas the protein level of sFAs in the peritoneal fluid samples and cleaved caspase-3 in ectopic and normal endometrial tissue samples were determined using the enzyme-linked immunosorbent assay and western blot, respectively. Furthermore, in silico analyses were performed to investigate protein–protein interactions as well as molecular function and cellular location of selected proteins. Statistical Analysis Used: The student’s t-test was used to analyse the difference between the means of the two groups. Results: The expression of FAS and sFas increased in endometriosis tissues as compared to the control group (P < 0.05). However, lncRNA FAS-AS1 and cleaved caspase-3 decreased in ectopic endometrial tissues compared to normal endometrial tissues and low lncRNA FAS-AS1 expression was correlated with disease stages. In addition, the in silico analysis revealed the importance of FAS/caspase3 in the biological processes involved in the development of endometriosis. Conclusion: The current study suggests that lncRNA FAS-AS1 may function as an ectopic endometriotic suppressor. Moreover, the results showed that severity of endometriosis is also closely correlated with the expression of lncRNA FAS-AS1 and sFAS.